An Iron Transporter Is Involved in Iron Homeostasis, Energy Metabolism, Oxidative Stress, and Metacyclogenesis in Trypanosoma cruzi - Dick, Claudia F.; Rocco-Machado, Nathália; Dos-Santos, André L. A.; Carvalho-Kelly, Luiz F.; Alcantara, Carolina L.; Cunha-E-Silva, Narcisa L.; Meyer-Fernandes, José R.; Vieyra, Adalberto (Frontiers in Cellular and Infection Microbiology, 2022)
The parasite Trypanosoma cruzi causes Chagas’ disease; both heme and ionic Fe are required for its optimal growth, differentiation, and invasion. Fe is an essential cofactor in many metabolic pathways. Fe is also harmful due to catalyzing the formation of reactive O2 species; for this reason, all living systems develop mechanisms to control the uptake, metabolism, and storage of Fe. However, there is limited information available on Fe uptake by T. cruzi. Here, we identified a putative 39-kDa Fe transporter in T. cruzi genome, TcIT, homologous to the Fe transporter in Leishmania amazonensis and Arabidopsis thaliana. Epimastigotes grown in Fe-depleted medium have increased TcIT transcription compared with controls grown in regular medium. Intracellular Fe concentration in cells maintained in Fe-depleted medium is lower than in controls, and there is a lower O2 consumption. Epimastigotes overexpressing TcIT, which was encountered in the parasite plasma membrane, have high intracellular Fe content, high O2 consumption—especially in phosphorylating conditions, high intracellular ATP, very high H2O2 production, and stimulated transition to trypomastigotes. The investigation of the mechanisms of Fe transport at the cellular and molecular levels will assist in elucidating Fe metabolism in T. cruzi and the involvement of its transport in the differentiation from epimastigotes to trypomastigotes, virulence, and maintenance/progression of the infection.